Promotion Strategy Of Pacu Jawi Event in Pariangan District, West Sumatra Province - Siska Mandalia; Taufik Hidayat; Elvina (Journal of Mandalika Review, 2023)
Introduction: This study aims to determine the promotion strategy for the Pacu Jawi (cow race) event in Pariangan District, West Sumatra Province. There are three indicators of the promotion strategy used to promote the Pacu Jawi event in Pariangan District, West Sumatra: identifying the target audience, designing messages, and choosing appropriate media. These three indicators need to be a concern to help the Youth and Sports Tourism Office in Tanah Datar Regency to attract tourists and compete with other tourism events in West Sumatra so that in the future, the Pacu Jawi Event is right on target, according to the needs and interests of tourists, and visitors who are targeted are more effective and efficient. Methodology: The research method used is a descriptive qualitative approach with a case study design. The subjects of this study consisted of six informants, two main informants from the Youth and Sports Tourism Office Tanah Datar Regency, one supporting informant from the chairman of the Pariangan District Tourism Travel Awareness Group (Pokdarwis), one Head of Pacu Jawi Association (Porwi), and two informants from the Travel Agents. Data collection techniques and data sources were carried out using interview methods with interview guidelines and documentation in the form of direct photos and voice recordings from the informants. Findings: The results of this study show that research informants identify target audiences using special techniques by expanding the selected audience based on tourist visits. Is there any increase or decrease? Identifying the target audience is also through the Pacu Jawi photography competition; the target is photographers and domestic tourists who can affect economic growth for residents and are expected to increase the amount of regional income because many tourists come from outside of the region. Besides that, designing messages by creating an attractive event calendar design and uploading it on social media, such as Instagram, every week for the Pacu Jawi event and making it a tour package is one of the strategies to promote the event. Another strategy is to spread messages through the event calendar, namely the flagship program of the Tanah Datar Regency Government, namely the One Nagari One Event Program. The flagship One Nagari One Event program has been facilitated by the Tanah Datar local government since 2022 to revive the tourism sector and rise from the impact of the COVID-19 pandemic. This program is expected to be able to attract tourists to Tanah Datar Regency, West Sumatra, Indonesia. In addition, traditional culture and traditions that have disappeared are now reappearing, and also through this program, it is possible to drive tourism and the creative economy. On this event calendar, there are black, red, and yellow symbols, which symbolize the Marawa (a tricolor flag consisting of three vertical charts showing the typical Minangkabau colors, that is black, red, and yellow) as the official flag of Minangkabau. In designing the message, it has fulfilled the aspects and paid attention to the content of the message to be disseminated. However, it should also be noted that before creating a message, it is important to use communicative sentences to make it easy for the audience to understand. Media selection is made personally and non-personally. Personal media is communication carried out face-to-face between two or more people as done by the Tourism, Youth and Sports Office of Tanah Datar Regency, which is attending events and promoting them directly through making videos containing information about the Pacu Jawi event. Meanwhile, non-personal communication is carried out indirectly or with the help of print / online media such as social media (Instagram, Facebook, TikTok), flyers, and posters. Conclusion: The Pacu Jawi Event Promotion Strategy in Pariangan Regency, West Sumatra Province, uses three indicators; the first is identifying the target audience using special techniques in determining the target audience by inviting photographers for the Pacu Jawi photo competition and classifying demographics that target audiences of all ages, genders, and professions. The second is designing messages with simple language, which does not mean simplifying the concept but presenting information in a way that is more easily understood by the audience and also telling an overview of the content of the philosophy of Pacu Jawi in Pariangan itself to attract tourists with events in Nagari Pariangan. The design of the message has a particular meaning and is different for each message conveyed because the message depends on the event to be promoted. Third, the selection of media used is based on print media such as posters and billboards and online media such as social media like Instagram, Facebook, Tanah Datar District Government website, TikTok and uploading documentary videos about the Pacu Jawi event and through radio broadcasts. Keywords: Promotion Strategy, Pacu Jawi, Event, Pariangan